Assessing care models implemented in primary healthcare for persons with dementia: a mixed-methods study protocol. Issue 5 (15th May 2020) - Vedel, Isabelle; McAiney, Carrie; Couturier, Yves; Pakzad, Sarah; Arsenault-Lapierre, Geneviève; Godard-Sebillotte, Claire; Sourial, Nadia; Simmons, Rachel; Bergman, Howard
Abstract : Introduction: Dementia is on the rise in Canada and globally. Ensuring accessibility to diagnosis, treatment and management throughout the course of the disease is a very significant problem worldwide. In order to provide comprehensive care to patients and their caregivers, enhancing primary care-based dementia care is seen as the way forward. In many Canadian provinces various collaborative care models (collCMs) anchored in primary care to improve dementia care have been developed and implemented. The overall objective of our research programme is to identify key factors for the successful implementation of collCMs, and to facilitate dissemination and scale-up of dementia best practices. Methods and analysis: We will use a convergent mixed-methods design. An observational study using chart review (2014–2016) and questionnaires (2014–2018; repeated in 2020) will measure application of guidelines and implementation of collCMs. This study will be complemented with a qualitative descriptive study using interviews (2017–2020) conducted in parallel. Quantitative and qualitative results will be further integrated using a matrix representing sites and findings. An integrated knowledge exchange strategy will ensure uptake by principal stakeholders throughout the research. Ethics and dissemination: Our study has been approved by all relevant ethics committees. Our dissemination plan follows an integrated knowledge transfer strategy using provincial, national and international councils. We will present the results individually to the clinical sites and then to these councils. Our research will be the first provincial and cross jurisdictional evaluation of primary care models for patients living with dementia, providing evidence on the ongoing debate on the respective role of clinicians in primary care and specialists in caring for patients with dementia.